Hepatitis B virus infection in medical and health care personnel. Issue 6312 (30th January 1982) - Callender, M E; White, Y S; Williams, R
Abstract : Analysis of 51 cases of hepatitis B virus infection in health care workers admitted as patients to the liver unit over seven years showed three healthy carriers of hepatitis B virus, seven cases of fulminant hepatic persistent hepatitis, 17 cases of chronic active hepatitis (of whom 11 had cirrhosis), and five cases of hepatocellular carcinoma. To date 11 of these patients have died. Only 15 of the 51 patients had a history of direct occupational exposure and only three patients could recall specific inoculation injuries. In contrast, the source of infection was apparent in 32 of 50 consecutive cases of fulminant hepatic failure or acute hepatitis B in nonmedical staff. Since specific inoculation injuries are not the usual mode of infection ion medical staff and since only a few of the patients who are hepatitis B virus carriers will be detected by selective screening of "high-risk" patients, the overall risk of infection can be reduced only by stricter precautions in the handling of any patient's blood and by the use of hepatitis B virus vaccines for medical staff at high risk.